Oil Rents Management and Distribution In the Global South - Malicha, Wario (Advances in Social Sciences Research Journal, 2018)
This paper investigates fiscal policy options and regulatory framework for harnessing resource rents from the oil industry. The aim is to demonstrate that for the nations of Global South to benefit from oil industry they have to adopt mechanisms of progressive extractive rents regime, better policies for oil resource funds, and regulation and proper control of state-owned enterprises. This has been a demanding task for the nations of the South due to weak pre-existing institutions, lack of implementation of fiscal rules and lack of political good will. Through a review of the literature, this paper concludes that developing states should focus on crafting country-fit fiscal policy decisions in revenue management, ensuring transparency and accountability in the institutions that convert the oil rents to sustainable development outcomes.